2015
DOI: 10.1111/jace.13565
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase and Solid‐State Simultaneous Mechanism for Two‐Step Carbothermal AlON Formation

Abstract: AlON powders were synthesized by two‐step carbothermal reduction nitridation method, which includes thermal treatment of Al2O3/C mixtures at 1200°C–1600°C for 2 h, followed by subsequent heating at 1750°C for 1.5 h in N2 flow. The effects of soaking temperatures of the first step on phase compositions and morphologies of the final products were investigated. It is found that the variation in precalcination does not have impact on phase compositions of the final products, which are all single‐phase AlON. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 38 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…As shown in Figure 5A, the original AlON powder has a step-shaped surface, which is a common characteristic of AlON powder. 24 For the powders heated at 800°C ( Figure 5B) and 1000°C ( Figure 5C), the surface was similar to that of the original one but somehow became smooth. When the heating temperature rose to 1150°C, a dramatic change can be observed that there were cracks and fine pores in the particle surface, as shown in Figure 5D.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in Figure 5A, the original AlON powder has a step-shaped surface, which is a common characteristic of AlON powder. 24 For the powders heated at 800°C ( Figure 5B) and 1000°C ( Figure 5C), the surface was similar to that of the original one but somehow became smooth. When the heating temperature rose to 1150°C, a dramatic change can be observed that there were cracks and fine pores in the particle surface, as shown in Figure 5D.…”
Section: Resultsmentioning
confidence: 81%
“…The morphologies of the oxidized AlON powders which were heated at different temperature in air, as well as the original one, are shown in Figure 5. As shown in Figure 5A, the original AlON powder has a step‐shaped surface, which is a common characteristic of AlON powder 24 . For the powders heated at 800°C (Figure 5B) and 1000°C (Figure 5C), the surface was similar to that of the original one but somehow became smooth.…”
Section: Resultsmentioning
confidence: 85%
“…On the other hand, when a rotation of 2 rpm was introduced, the obtained powder was a mixture of α‐Al 2 O 3 and AlN, with an appearance of aluminum oxynitride (AlON) phase. It is well known that AlON is synthesized from a mixture of γ‐Al 2 O 3 and AlN 45–51 . γ‐Al 2 O 3 has been reported to be an intermediate phase in AlN gas reduction–nitridation, from which aluminum nitride is obtained 24 .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that AlON is synthesized from a mixture of γ-Al 2 O 3 and AlN. [45][46][47][48][49][50][51] γ-Al 2 O 3 has been reported to be an intermediate phase in AlN gas reductionnitridation, from which aluminum nitride is obtained. 24 In other studies, it has been shown that γ-Al 2 O 3 /AlN mixture can take place earlier than 1200 • C in AlN synthesis via NH 3 and C 3 H 8 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in powders. Such terraces were caused by the gas reaction during the powder synthesis process, which has already been investigated in detail [31]. Due to the highly symmetrical face-centered cubic (FCC) crystal structure of AlON, the grains usually grow in preferential orientations.…”
Section: Twins In Synthetic Alon Powdersmentioning
confidence: 99%